ANALISIS SENSITIVITAS NILAI INVESTASI TERHADAP ANNUAL BENEFIT PROYEK PEMBANGUNAN PASAR DI INDRAMAYU - Fajar, Ibnu; Hasyim, Wachid; Suhana, Nono (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Investment is the activity of placing capital with the aim of obtaining profits in a certain period; in this case, the Indramayu Regency government will build a market building for investment and provide a place for traders. This study aims to determine the sensitivity of investment value to annual benefits. Data obtained from interviews with the head of market management and related parties. The research method used is the descriptive analysis method using sensitivity analysis with two alternatives. Alternatives are arranged based on the investment value and operational period, namely alternative A with a capital of Rp. 39,782,240,911 and an investment period of 20 years, an interest rate of 12%, and alternative B with a capital of Rp. 42,067,040,911 and an investment period of 25 years, an interest rate of 12%. Based on the results of the analysis and discussion, it can be concluded that alternative A has several investment parameter values, namely NPV 43,960,356,295, BCR (Benefit Cost Ratio) 1.10%, IRR (Internal Rate of Return) 2.73%, and Payback Period (PBP) in year 11, while in alternative B, the value of several parameters, namely NPV 50,056,649,833, BCR 1.53%, IRR 15.63%, and PBP, occurs in year 11. The results of the analysis of the investment value of the annual benefit of each alternative are sensitivity A at Rp. 48,459,760,321, and sensitivity B at Rp. 53,277,732,244.